2021
DOI: 10.3126/jpahs.v8i2.37287
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough infection after COVID-19 vaccination: A threat for Nepal due to SARS-CoV-2 variants circulating in 2nd wave ravaging India

Abstract: After a year of the COVID-19 pandemic, the meta-analysis in Dec 2020 did not support its reinfections. Now it’s clear that not only reinfection following earlier exposure is a reality, but also breakthrough infections after vaccinations have been increasingly reported. A breakthrough infection means that the infection has broken through the protection provided by the vaccine. The course of the disease, strict observation for preventive measures, together with safe vaccines is necessary long-term solutions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In response to this unprecedented challenge, many countries implemented nonpharmaceutical interventions (NPIs) such as physical distancing, remote work, face mask-wearing, and school and workplace closures while awaiting the widespread distribution of effective vaccines [9][10][11][12][13] . However, despite the availability of vaccines, the emergence of new variants and waning immunity has led to ongoing breakthrough infections and reinfections, contributing to a persistently challenging situation [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…In response to this unprecedented challenge, many countries implemented nonpharmaceutical interventions (NPIs) such as physical distancing, remote work, face mask-wearing, and school and workplace closures while awaiting the widespread distribution of effective vaccines [9][10][11][12][13] . However, despite the availability of vaccines, the emergence of new variants and waning immunity has led to ongoing breakthrough infections and reinfections, contributing to a persistently challenging situation [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…9 According to the WHO Program for International Drug Monitoring (PIDM) database, till date a total of 335,052 re-infection cases and 6470 vaccine breakthrough cases have been reported 10 while Indian studies alone account for a high rate of re-infection (incidence range of 4.5-34.8%) and breakthrough infections (incidence range of 0.4−13%) among HCWs. [11][12][13][14] On the 6th of November 2020, the Centers for Disease Control defined 'prolonged contact' as the cumulative period of exposure of 15 min or more to an infected person(s) within a period of 24 h. 15 This ensures the safety concerns of HCWs, who daily work in a highly infectious environment (including many subclinical and undiagnosed cases).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine breakthrough COVID-19 infections are defined as an individual testing positive for SARS-CoV-2 by RRT-PCR or rapid antigen test (RAT) any time after 14 days of receiving one dose of any of the licensed COVID-19 vaccines [8] . Initially very low rate of breakthrough cases was reported but many studies conducted in different parts of the world showed an incidence range of 0.04% to 13% [9] . According to the World Health Organization (WHO) Programme for International Drug Monitoring (PIDM) database; a total of 5130 vaccine breakthrough cases have been reported to date [10] .…”
Section: Introductionmentioning
confidence: 99%